Anatomic measurements of teeth extracted from Filipinos aged fifteen to thirty five - Velasco, May Magdalena I.; Jimena, Edna M. (Adviser)+.
This paper attemps to establish average measurement of Filipinos with the objectives to determine any difference in the tooth length, crown height and root length among the age groups and between sexes and to compare Filipinos' measurements with those of the Caucasians done by Bjorndal. The materials in this study consisted of 620 teeth extracted from Filipinos collected from the PGH-OPD dental dispensary, UP College of Dentistry and private dental clinics. Results showed that there is no sexual dimorphism exists in teeth among Filipinos, the crown height decreases as the age increases. At the age range of 15 to 21, Caucasians (males) have longer teeth than Filipino males.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.